2011
DOI: 10.1016/j.jtrangeo.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Using GIS to visualise and evaluate student travel behaviour

Abstract: Using GIS to evaluate travel behaviour is an important technique to increase our understanding of the relationship between accessibility and transport demand. In this paper, the activity space concept was used to identify the nature of participation in activities (or lack of it) amongst a group of students using a 2 day travel-activity diary. Three different indicators such as the number of unique locations visited, average daily distance travelled, and average daily activity duration were used to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 58 publications
0
43
0
1
Order By: Relevance
“…Traditionally, the measures of deprivation have attempted to identify and assess these attributes [39]. These are often referred to as different dimensions (or domains) of deprivation such as economic, social, political, personal, living space, mobility impairment, and geographical isolation [8,29,[40][41][42][43][44].…”
Section: Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, the measures of deprivation have attempted to identify and assess these attributes [39]. These are often referred to as different dimensions (or domains) of deprivation such as economic, social, political, personal, living space, mobility impairment, and geographical isolation [8,29,[40][41][42][43][44].…”
Section: Conceptmentioning
confidence: 99%
“…This work has found that the commuting distance is shorter for married women than married men and the mobility is relatively stable over time for married women who are in higher paid jobs (interaction between gender and employment). Kamruzzaman et al [41] have used average daily distance travelled as a measure of student mobility and found that students who live outside of the limits of a demand responsive service have a significantly higher level of mobility (as spatial disaggregation). Therefore, it appears that the operationalised examples of personal mobility-based measures using the concept of activity spaces overcome some of the identified weaknesses of the traditional mobility-based measures such as socioeconomic (e.g., male, female, disabled, and children) disaggregation, and spatio-temporal disaggregation of the availability/use of transport services.…”
Section: Personal Mobility-based Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also beneficial for passengers, if a good visualization of alternative routes is presented. Collecting passengers' routes the operators can derive mobility patterns (Kamruzzaman et al, 2011).…”
Section: Trends Of Developmentmentioning
confidence: 99%
“…Despite intensive application in such different research fields as transport planning, risk analysis, suitability analysis, land use planning, and water management (Ceballos-Silva and Lopez-Blanco, 2003;Dai et al, 2001;Kamruzzaman et al, 2011;Makropoulos and Butler, 2006;Simon et al, 2004;Zucca et al, 2008), the application of the SMCE in resolving boundary conflicts has received little attention in the literature. Sharifi et al (2002) have applied the SMCE to locate a boundary between the Tunari National Park and Cochabamba city in Bolivia.…”
Section: Municipal Boundary Conflictmentioning
confidence: 99%